Sustainable measures to manage social tension - Vittal, N. (2002)
Causes of social tension often creep into our society as a matter of historical tradition, religious parochialism, short-sighted policies and vested interests. This article analyses the various causes and shades of social tension and, based on his long experience in public service, suggests ways and means to achieve sustainable solutions to these problems. - Reproduced.
Keywords: Social conflicts